Analysis of Water Availability in Tilong Reservoir, East Nusa Tenggara Due to Climate Change - Bees, Azarya; Mooy, Merzy (Fakultas Teknik, Universitas Brawijaya, 2024)
This study aims to determine the availability of Tilong Reservoir inflow related to climate change. Water availability can be seen from the high inflow into the reservoir, obtained using the Mock model to simulate the inflow. The modeling results using the Mock model in the historical period are then compared with the results of future projections using GCM CanESM2 data from SSP119 to SSP585 scenarios. The historical period is modeled using rainfall from 2000 to 2019, while the projection period is divided into two periods, namely the 2030s (2020-2039) and 2050s (2040-2059). The projection results show that the highest increase in rainfall will occur in the SSP245 scenario for the 2030s and 2050s. The highest increase in future rainfall occurs in June, while the highest decrease occurs in August. With the increase in rainfall, there will also be an increase in inflow into the Tilong Reservoir, especially in December, which is more than 100% for each SSP scenario. In addition, an increase in water availability can also be seen by an increase in the dependable discharge, especially at SPP245, where there was an increase in the highest dependable discharge of 64.23% in the 2030s and 76.80 in the 2050s. The increase in dependable discharge is seen to positively impact the water availability of the Tilong Reservoir. However, it is necessary to pay attention to the reservoir’s operational pattern so that the existing water can be used optimally.